The presence of fungi on contact electrical stimulation electrodes and ultrasound transducers in physiotherapy clinics - Mobin, Mitra; Borba, Cintia de Moraes; de Moura Filho, Oseas F.; de Melo Neto, Antonio Quaresma; Valenti, Vitor E. [UNESP]; Marques Vanderlei, Luiz Carlos [UNESP]; de Abreu, Luiz Carlos (Elsevier B.V., 2011)
Objectives To evaluate the presence of fungi on contact electrodes and ultrasound transducers from physiotherapy clinics.Design Quantitative study conducted at the Laboratory of Microbiology and Immunology, Faculty of Health Sciences and Technology of Piaui - NOVAFAPI, Teresina, Brazil.Setting Sample collection was performed in 10 clinics ( 20 ultrasound transducers and 20 contact electrodes).Main outcome measures Swabs were soaked with saline solution, inoculated in culture and incubated for filamentous fungi and yeast growth.Results Fourteen taxons were identified: Acremomium hyalinulum (Sacc.), Aspergillus terreus, Candida albicans, Cladosporium cladosporioides, Cladosporium elatum, Cladosporium oxysporum, Cladosporium sphaerospermum, Cladosphialophora bantiana, Curvularia clavata, Curvularia senegalensis, Fusarium oxysporum, Penicillium decumbens, Scopulariopsis candida and Sporothrix schenckii. Aspergillus terreus, Cladosporium oxysporum, Sporothrix shenckii and Candida albicans were found most often on contact electrodes, and Penicillium decumbens and Cladosporium cladosporioides were found most often on ultrasound transducers.Conclusion Fungi were found on all of the contact electrodes and ultrasound transducers. Physiotherapy professionals need to improve the disinfection procedures for this equipment. (C) 2010 Chartered Society of Physiotherapy. Published by Elsevier Ltd. All rights reserved.
Keywords: Fungi; Physical therapy (specialty); Electrodes; Ultrasonics; Infection